Institutional dynamics and impact on capital formation: evidence from Namibia and Tanzania - Zaaruka, Benethelin P. (My University, 2013)
The purpose of this thesis is to examine the impact of institutions on fixed capital accumulation over time in two developing countries, both former German colonies: Namibia and Tanzania. This is motivated by two recent underpinning theories: the new institutional theory, which views institutions as fundamental determinants of economic outcomes and income variations among countries (the institutional hypothesis); and the theory of irreversible investment under uncertainty, which emphasis the impact of uncertainty on investment and capital-stock accumulation. The first part of the thesis deals with the measurement and definitions of institutions. Empirical measures of political and economic institutions have been previously produced; however, most cover short periods of time. The short time span of the institutional indices makes them practical in cross-countries and panel studies, rather than in country-specific studies. The importance of country-specific studies is underscored by the notion that different historical paths led to different ways of organising economic activities and political structures, yielding the differences in economic development across countries. To overcome this challenge, this thesis presents a database on institutional measures for Namibia and Tanzania for the period 1884 to 2009. These indicators are used to assess the nature of political and economic institutional transformation from the colonial legacy to the modern outcome, using Namibia and Tanzania as a natural experiment. Relying on archival information on formal laws in Namibia and Tanzania, the thesis constructs institutional indicators that are de jure in nature representing political freedom, property rights and judicial independence. These allow for the assessment of rules the game, rather than outcome. The formal codification of rights and freedoms is of little significance if those rights cannot be enforced. Therefore, the de facto element is also considered through the construction of separate indicators on political instability and judicial independence. A clear theoretical framework on each indicator provides the selection and combination of each sub-component. A meaningful composite measure is based on the techniques of principal components and factor analysis. v The thesis argues that despite changes in colonial identity in these countries (i.e. German, then British or South African), the broader framework of institutions remained partly the same, particularly in the case Namibia. It is true that, with the attainment of independence in Namibia, many institutions did change, particularly in the areas of political freedom, and judicial and political instability. Measures such as property rights, on the other hand, are slow to change. However, the overall long-lasting effect of these colonial institutions on economic outcomes remains an empirical question. Similarly, the case of Tanzania reflects the notion of institutional persistence as the country continued to undermine political freedom even after the attainment of independence. Tanzania is among the few countries which adopted a constitution without a bill of rights at independence. Also, the new indicators for both countries, while covering a long time period (1884–2009), correlate fairly well with some of the widely used institutional indices produced by Freedom House and the Heritage Foundation. The second part of thesis establishes the impact of institutional variables on capital accumulation in Namibia and Tanzania, applying the Johansen Vector Error Correction Model (VECM) technique. The data span for Namibia is from 1923 to 2009, and that for Tanzania is from 1946 to 2009. The findings highlight the importance of uncertainty (political instability) in explaining capital accumulation over time in Namibia. The results also show that other institutional variables are important in explaining uncertainty. Rising levels of property rights and political rights lower political instability in Namibia. The empirical evidence for Tanzania indicates the importance of property rights in explaining capital accumulation over time. The most interesting result is the importance accorded to the judicial independence, which showed a positive correlation to gross domestic product (GDP). It is also shown that other institutional variables (property rights and political rights) have a positive correlation to judicial independence. A further finding is that uncertainty (political instability) has a negative effect on economic development over time in Tanzania.
Keywords: Economic development; Namibia; Tanzania; Capital; Institutions; Measurement